Reimagining Barbie. A Feminist Analysis of Iconography and Consumerism in the Age of Gender Reevaluation - Bobaru Nicolae (Gender Studies)
This paper critically analyses the motion picture Barbie (2023) within the context of gender discourse and consumer culture, exploring its dual role as a feminist artefact and a commodity. Drawing on seminal feminist theories, including Betty Friedan’s critique of domesticity and Naomi Wolf’s exploration of beauty as a social construct, alongside other scholarly works, including Robin Gerber’s historical account of Barbie’s creation, J. Lenore Wright’s exploration of body archetypes, Mary F. Rogers’ critique of Barbie culture, Juliette Peers’ fashion doll evolution, and Kim Toffoletti’s posthuman feminist perspective, the study interrogates the film’s portrayal of feminist ideals against its commercial backdrop. By examining Barbie’s impact on gender identity, societal norms, and consumer behaviour, the paper contributes to the nuanced debate on the interplay between feminist representation and media commodification, offering insights into the complexities of engaging with feminist themes in a consumer-driven landscape.